IMPLEMENTASI KARTU SEMARANG SEHAT (JAMKESMASKOT) DI KOTA SEMARANG - Tambunan,, Yosita Meilani; Suryaningsih, M. (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Health is a fundamental right for citizen in this nation. Every body has a right of the health care and are guaranteed by the nation. The State is obligated to meet the needs and health services for all citizens including for the poor and couldn't afford it. The policy of granting health coverage for the poor and can't afford is one of the policies that can guarantee the granting of free health services to the poor and can't afford that generally have difficulties to be able to finance any treatment and health services for himself. The purpose of this policy is to provide services in the field of health care to the poor and cannot afford, especially in the Semarang city. This purpose of this research to describe how the implementation of the Semarang Healthty Card as the program is implemented to be able to achieve the purpose of the Mayor Regulation number 28 in 2009. In addition, also to find out the factors that encourage and impede the provision of the Semarang Healthty Card in Semarang city by using the implementation model of Edward III that has 4 variables that affect in the implementation of a policy, include: communication, resources, disposition/implementing attitude and bureaucratic structure. The results show that the implementation of the Semarang Healthty Card / Jamkesmaskot in Semarang city was implemented correctly, but still has a constraint in some thing like still the presence of the target user is not appropriate, a health security card ownership is more than two, lack of socialization of health services and the lack of public knowledge about the Semarang Healthty Card. Recommendations from the results of this research are to make the correct data collection for more appropriate to the community poor and cannot afford, socialization from The Health Departmen of Semarang city for the right target of all the poor and could not afford, as well as to the hospital so that it can continue to serve the public with a maximum. In addition, the Health Departmen of Semarang city expends the Semarang Healthty Card to facilitate the acces of people in helath services. The implementation actors has to improve the coordination of their respective as the implementation actors of Semarang Healthty Card / Jamkesmaskot.